Women activism in the former Yugoslav States - Erbay, K. Aslı. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
This study questions what kind of factors had an impact on women's organizing during and after the Yugoslav war of 1991-1995. The feminist movement, the Mother's Movement and the anti-war movement in 1990s and their effect on women's organization are the subjects of this thesis. The argument of this study is that feminist movement of 1980s and anti-war movements mobilized women and paved the way for their self organization in the form of women's NGOs during and after the Yugoslav war. Women were mobilized in anti-war and self-help groups in the former Yugoslav states, where actual armed conflicts took place. The number of women's organizations in these states continued to increase after the war. This study reflects on the women's organization in the public sphere as a consequence of anti-war and feminist movements, which are examined from the social movement theory perspective. The thesis attempts to show that the women became more active actors in public life during and after the war and women's activism should not go unnoticed. During my research I gathered data from secondary sources (books, academic articles, internet web-pages, conference papers, field reports) and from primary resources (interviews with women activists in Croatia and Macedonia).
Keywords: Women -- Former Yugoslav republics -- History.; Feminism -- Former Yugoslav republics -- History.; Yugoslav War, 1991-1995 -- Protest movements.